1969
DOI: 10.1111/j.1365-2141.1969.tb05667.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thrombocytopenia on Megakaryocytopoiesis

Abstract: Summary. Megakaryocytopoiesis was studied in rats made thrombocytopenic by daily injections of platelet‐specific antiserum. Tritiated thymidine was injected 24 hours after the first antiserum and rats were killed at intervals up to 72 hours after the thymidine. Megakaryocyte number and mitotic index were determined on sections of bone marrow; the labelling index (per cent of cells labelled) and frequency of megakaryocytes in morphologic compartments were determined in autoradiograms of marrow smears. Thrombocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
3

Year Published

1970
1970
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(20 citation statements)
references
References 19 publications
3
14
0
3
Order By: Relevance
“…If one assumes that thrombopoietin accelerates thombocytopoiesis by acting at the level of the morphologically unidentified megakaryocyte precursor cell compartment (pluripotential or polyploid) and that the cell generation time in this compartment is approximately the same as that for the proliferating megakaryocyte compartment (9.5 h) [9], then one might expect to observe increase levels of thrombopoietin preceding a 'reactive' megakaryocytosis. Such a megakaryocytosis occurs within 24-72 h after the induction of thrombocytopenia [4,7,10].…”
Section: Discussionmentioning
confidence: 99%
“…If one assumes that thrombopoietin accelerates thombocytopoiesis by acting at the level of the morphologically unidentified megakaryocyte precursor cell compartment (pluripotential or polyploid) and that the cell generation time in this compartment is approximately the same as that for the proliferating megakaryocyte compartment (9.5 h) [9], then one might expect to observe increase levels of thrombopoietin preceding a 'reactive' megakaryocytosis. Such a megakaryocytosis occurs within 24-72 h after the induction of thrombocytopenia [4,7,10].…”
Section: Discussionmentioning
confidence: 99%
“…41 Platelets produced under conditions of stimulated platelet production, called "stress" platelets by Penington et al 38 show an increase in the MPV compared with normal circulating platelets. 37,38,42,43 There is strong evidence indicating that MPV is an important biological variable 44 and that large platelets have a higher thrombotic potential. Karpatkin et al 8,23,45,46 and Corash et al 47 have demonstrated that large platelets are metabolically and enzymatically more active than small platelets as assessed by ex vivo aggregometry.…”
mentioning
confidence: 99%
“…The relatively few M-I cells found on the 6th day following the last injection of the cytotoxic agents may still be due to the drug-induced retardation of the proliferation of the megakaryo cyte precursors, although the low M-I and high M-I 11 percentage found at that stage following Ara-C and D administration might reflect a shortened megakaryocyte maturation time, as observed by O d ell et al [12] after thrombocytopenic episodes in rats following administration of antiplatelet serum. The latter explanation would be compatible with the rise in the pla telet count observed at this stage in the Ara-C-treated and D-treated rats.…”
Section: Discussionmentioning
confidence: 72%